1998
DOI: 10.1677/joe.0.1590179
|View full text |Cite
|
Sign up to set email alerts
|

Fetal expression of GnRH and GnRH receptor genes in rat testis and ovary

Abstract: The identification of gonadal gonadotropin-releasing hormone receptors (GnRH-R) and evidence of direct inhibitory effects of GnRH agonists upon steroidogenesis in adult rat gonads, lend credence to a putative intragonadal role of a locally secreted GnRH or GnRH-like peptide. Using reverse transcription-polymerase chain reaction followed by Southern blot hybridization and sequencing, we identified, both in the ovary and in the testis of fetal and adult rats, a fully processed GnRH messenger RNA (mRNA), the sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 57 publications
2
46
0
Order By: Relevance
“…To date, based on functional and morphological criteria, it is believed that these two cell populations represent two distinct lineages (O'Shaughnessy et al 2006). Using RT-PCR approaches in rat foetal gonads, we have previously identified Gnrh and Gnrhr transcripts as soon as 14.5 dpc (Botte et al 1998). Interestingly, the foetal expression pattern of Gnrhr in the testis displayed an acute rise at late gestation starting at 20.5 dpc that corresponds to the onset of testis responsiveness to GnRH (Habert et al 1991, Habert 1992).…”
Section: Introductionmentioning
confidence: 99%
“…To date, based on functional and morphological criteria, it is believed that these two cell populations represent two distinct lineages (O'Shaughnessy et al 2006). Using RT-PCR approaches in rat foetal gonads, we have previously identified Gnrh and Gnrhr transcripts as soon as 14.5 dpc (Botte et al 1998). Interestingly, the foetal expression pattern of Gnrhr in the testis displayed an acute rise at late gestation starting at 20.5 dpc that corresponds to the onset of testis responsiveness to GnRH (Habert et al 1991, Habert 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The source of GnRH-IR and its molecular characteristics should be clarified in further studies. GnRH-like protein, GnRH mRNA, specific highaffinity binding sites for GnRH, and GnRH receptor mRNA have been demonstrated to be present in rat ovarian tissues [1,[6][7][8][9][10][11]. A previous study reported that the expression of GnRH receptor mRNA in the rat ovary varies during the reproductive cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of GnRH-like protein, GnRH mRNA, specific high-affinity binding sites for GnRH, and GnRH receptor mRNA have been demonstrated in the rat ovary [1,[6][7][8][9][10][11]. The bovine granulosa cells also contain higher concentrations of GnRH-like protein than other ovarian and extraovarian tissues [12].…”
mentioning
confidence: 99%
“…In the testes, GnRH mRNA is expressed in Sertoli cells while the GnRHR is expressed in the Leydig cells by RT-PCR (Bahk et al 1995, Botte et al 1998. In early fetal development in the rat, GnRH mRNA expression in the testis precedes that in the ovary, followed by GnRHR expression.…”
Section: Gnrh and Gnrhr In Extra-hypothalamic Tissuesmentioning
confidence: 99%